Targeting Th17 Cells with Small Molecules and Small Interference RNA - Hui Lin; Pingfang Song; Yi Zhao; Li-Jia Xue; Yi Liu; Cong-Qiu Chu (Hindawi Limited, 2015)
T helper 17 (Th17) cells play a central role in inflammatory and autoimmune diseases via the production of proinflammatory cytokines interleukin- (IL-) 17, IL-17F, and IL-22. Anti-IL-17 monoclonal antibodies show potent efficacy in psoriasis but poor effect in rheumatoid arthritis (RA) and Crohn's disease. Alternative agents targeting Th17 cells may be a better way to inhibit the development and function of Th17 cells than antibodies of blocking a single effector cytokine. Retinoic acid-related orphan receptor gamma t (RORγt) which acts as the master transcription factor of Th17 differentiation has been an attractive pharmacologic target for the treatment of Th17-mediated autoimmune disease. Recent progress in technology of chemical screen and engineering nucleic acid enable two new classes of therapeutics targeting RORγt. Chemical screen technology identified several small molecule specific inhibitors of RORγt from a small molecule library. Systematic evolution of ligands by exponential enrichment (SELEX) technology enabled target specific aptamers to be isolated from a random sequence oligonucleotide library. In this review, we highlight the development and therapeutic potential of small molecules inhibiting Th17 cells by targeting RORγt and aptamer mediated CD4+ T cell specific delivery of small interference RNA against RORγt gene expression to inhibit pathogenic effector functions of Th17 lineage.